Mapping of Potential Flood Prone Areas Using the Scoring Method and Overlay in Batanghari Regency - Melka Sintia Siburian; Aminoto, Tugiyo; Hamdi, Husnul (The Physical Society of Indonesia, 2026)
Mapping of potential flood-prone areas using scoring and overlay methods in Batanghari Regency has been carried out. This study aims to determine the level of flood vulnerability and the distribution of flood-prone areas. The parameters used are rainfall parameters, soil type parameters, river distance parameters, slope parameters, land cover parameters, and elevation parameters. The methods used are scoring and overlay methods with the assistance of ArcGIS 10.8 software. The level of flood vulnerability is classified into three categories: not vulnerable, vulnerable, and highly vulnerable. The results obtained in this study show that the majority of Batanghari Regency has a flood vulnerability level in the not vulnerable class, covering an area of 397,158.03 Ha (72%), with areas in the vulnerable category covering 132,119.089 Ha (24.22%), and highly vulnerable areas covering 15,380.96 Ha (2.82%). In contrast, the area that is relatively safe from flooding is the Bajubang District, which covers an area of 102,592.1 hectares (90.17%). This indicates that some areas of Batanghari Regency are prone to flooding, making it very important to take disaster mitigation actions in the Batanghari Regency.